ChemInform Abstract: Electronic and Steric Effects on the Intramolecular Schmidt Reaction of Alkyl Azides with Secondary Benzyl Alcohols. Issue 27 (8th July 2014) - Sun, Xiaowei; Gao, Chengzhe; Zhang, Fan; Song, Zhuang; Kong, Lingyi; Wen, Xiaoan; Sun, Hongbin
Abstract The intramolecular Schmidt reaction of azido secondary alcohols is investigated.